The Effect of Groundnut Shell Ash on Soil Stabilization - Pakir, Faizal (Journal of Sustainable Underground Exploration, 2022)
The purpose of this study was to focus on how the groundnut shell ash affect the soil stabilization. Groundnut shell ash was used in this study to replace the excessive reliance on industrially created soil enhancing chemicals (cement, lime, and so on) has kept the cost of stabilizing a road high. It was determined that groundnut shell ash may be used and effective as a soil stabilizing component after studying the stabilization of black cotton soil using groundnut shell ash. The ideal usage of groundnut shell ash applied to the soil is 6 percent. Particularly in engineering projects on poor soils, where it may be utilized to replace deep/raft foundations, groundnut shell ash and waste fibre reinforced soil can be an excellent ground improvement option. This can save both money and energy. The process of stabilizing foundation soils to attain desired characteristics or to improve the strength and durability of a less stable soil is known as stabilization. Differential expansion and contraction are possible when a soil’s moisture content fluctuates. It is usually required to stabilize them in order to lessen volume fluctuations and strengthen them so that they can withstand the applied loads even when saturated.